048. Roux-En-Y Duodenojejunostomy as Surgical Treatment for Congenital Duodenal Obstruction: A Case Report - Ruhimat, Albireza; Yani, Ahmad (JBN (Jurnal Bedah Nasional), 2024)
Background : Congenital duodenal obstruction is an anatomical abnormality in newborn. Various intrinsic and extrinsic etiologies can cause duodenal obstruction. The surgical treatment that commonly performed on duodenal obstruction in neonates is duodenoduodenostomy. However, several etiologies conditions such as preduodenal portal vein (PDPV) and pancreatic annulare cause duodenoduodenostomy is nearly impossible to be performed, so an alternative treatment is necessary. Case: This case describes female neonate with congenital duodenal obstruction which had been suspected since in pregnancy due to polyhydramnios, an OGT was installed with greenish yellow residue after the baby was born. Based on abdominal x-ray examination, a double bubble appearance was seen. The patient then underwent surgery when he was 5 days old. Intraoperatively, there was PDPV and pancreas annulare covering the 3rd-4th part of duodenum, so it was decided to perform Roux-en-y duodenojejunostomy. Conclusion: In patients with congenital duodenal obstruction with special etiology and anatomy such as PDPV and pancreatic annulare, it is possible to perform a roux-en-y duodenojejunostomy. Even though this operation is rarely performed on neonate and more common in adult patients, it can be an alternative in cases of congenital duodenal obstruction.